Pulse consumption and demand by different population subgroups in Uganda and Tanzania - Larochelle, Catherine; Katungi, Enid M.; Cheng, Zhen (International Center for Tropical Agriculture, 2017)
In recent years, the strategic importance of pulses in combating malnutrition and addressing health problems associated with overnutrition and obesity has been well acknowledged. However, previous research emphasized the production side and little is known about pulse consumption patterns by different groups of people. This study investigated pulse consumption patterns and demand by different socioeconomic groups in rural and urban localities of Uganda and Tanzania. Using the data compiled in the Living Standards Measurement Study-Integrated Surveys on Agriculture (LSMS-ISA) that are nationally representative of urban and rural households in Uganda and Tanzania, the study investigates the economic, temporal and spatial dimensions of pulse consumption and used econometric methods to evaluate the responsiveness of pulse demand to price and income changes. A two-stage censored food demand system was estimated to obtain consistent and unbiased unconditional expenditure and price elasticities for food and several food categories, including common bean in Uganda and pulses in Tanzania. Results indicate that consumption of pulses tend to increase with wealth and during harvesting periods as well as being higher in locations where production is also high. This emphasizes the important role that increased production of pulses could play in boosting consumption. Per capita consumption and contribution of pulses to protein in both countries is high. For example, in Uganda, bean contribute an average of 14.4 g of protein per person per day in rural areas, which is equivalent to 24% of the total daily per capita protein intake. In both countries, the poorer and wealthier households purchase a sizeable share of their consumed pulses. Pulse consumers are price sensitive and there is limited substitution for pulses, which suggests that price increase poses a risk for the nutritional security of the poor. Although projections in demand and supply growth rates indicate that supply might grow faster than demand, exports from both countries are growing faster than supply and this is likely to put pressure on domestic prices and further constrain demand among poorer households. Therefore, it is important to act now to avoid possible reduction in pulse consumption by poorer households that could lead to higher prevalence of malnutrition. Investment in agricultural research will be crucial such that farming households can adapt to a changing climate while increasing pulse productivity.